1976
DOI: 10.1139/v76-173
|View full text |Cite
|
Sign up to set email alerts
|

Empirical equations for predicting 13C chemical shifts in nuclear magnetic resonance spectra of certain types of amino acids

Abstract: 13C chemical shift data were obtained for amino acids related to glycine which had the following types of substituents on C-2: alkyl, branched chain alkyl, ω-amino alkyl, and ω-guanido alkyl. Such data were obtained for aqueous solutions at a pH between the pK values of the carboxyl and 2-amino groups (zwitterion form). The data were subjected to graphical and statistical analysis to obtain separate predictive equations for C-1, C-2, and other carbon atoms. Data for the change in chemical shifts on titration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…acids (Suprenant et al, 1980;Rabenstein & Sayer, 1976;MacDonald et al, 1976;Batchelor, 1975;Batchelor et al, 1975; Horsely & Sternlicht, 1968; Horsley et al, 1970). Data for glycine and other amino acids in aqueous solutions at different pHs are reported, and most amino acids by 13C NMR have a constant deshielding of = 2.4 for the ionization of the COOH group.…”
Section: Resultsmentioning
confidence: 99%
“…acids (Suprenant et al, 1980;Rabenstein & Sayer, 1976;MacDonald et al, 1976;Batchelor, 1975;Batchelor et al, 1975; Horsely & Sternlicht, 1968; Horsley et al, 1970). Data for glycine and other amino acids in aqueous solutions at different pHs are reported, and most amino acids by 13C NMR have a constant deshielding of = 2.4 for the ionization of the COOH group.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of the remaining high-field proton and carbon signals with the literature data for amino acids (MacDonald et al, 1976) showed that compound 1 contained a substructure similar to the amino acid isoleucine, but in a reduced way, isoleucinol, as 2D experiments revealed. The connectivities observed in the HMBC experiment are shown in Fig.…”
Section: Resultsmentioning
confidence: 81%
“…The 2D NMR spectroscopic experiments showed that all the correlations in the high field region were merely duplicated and partially overlapped. Furthermore, the available 13 C NMR spectroscopic data for amino acids (MacDonald et al, 1976) suggested that 1 and 2 were a 3:1 mixture of C-2 epimers, i.e. D-allo-IleOH:L-IleOH or L-allo-IleOH:D-IleOH, indicating that the major epimer was either D-allo or L-allo-IleOH, whereas the minor component was L-or D-IleOH.…”
Section: Resultsmentioning
confidence: 99%
“…13 C-NMR of the side product was in good agreement with the data given for 2,4-diaminobutyric acid (10). 15 Due to compound 10, being the reduced derivative of 2, we suppose that compound 10 is formed by the reduction of the CN group. NMR analysis showed the ratio of the products as 2:10 = 95:5.…”
Section: -Amino-3-cyanopropanoic Acid (β-Cyano-ʟ-alanine) (2)mentioning
confidence: 99%
“…In this context, carbobenzoxy-ʟ-asparagine 3 , trityl-ʟ-asparagine 4 , BOC-ʟ-asparagine 5 , (o-nitrophenylsulfenyl)asparagine 6 , and 3-amino-2-oxetanone salts 7 were used as the key compounds in the syntheses of β-cyanoalanine. β-Cyanoalanine labeled with 14 C or 15 N in the cyano group was prepared using immobilized cyanoalanine synthase (EC 4.4.1.9). 8 14 C-and 15 C-labeled β-cyano-ʟ-alanine were prepared by cyanidation of labeled cysteine catalyzed by cyanoalanine synthase.…”
Section: Introductionmentioning
confidence: 99%